Ônus da prova em ações de alimentos: distribuição dinâmica e seus desafios - Reina, Kátia Vilhena (2023)
The purpose of the present work is to present a reflection on the subject that emerged from numerous debates and questions experienced in the daily lives of lawyers who work in the family area, who face constant challenges in the context of to ensure effective jurisdictional provision in food stocks. These challenges arise, among other aspects, from the evidence necessary for the instruction and development of the action, which is of singular importance in judicial proceedings. Evidence, as will be better explored throughout this work, is of singular importance in judicial proceedings, without which effective and fair adjudication is impossible. As a result of this relevance in the procedural scope, the present work dealt with the burden of proof and its consequences in the context of maintenance actions. In addition, the present work aims to demonstrate the challenges and relevance of applying the dynamic distribution of the burden of proof, and how this institute has a unique role in guaranteeing access to justice and fundamental rights related to the family